Zebrafish aversion to infrasound in an open field test - Scatterty, Kale R.; Pitman, Taylor; Eckersley, Tristan; Schmaltz, Rodney; Hamilton, Trevor J. (Frontiers in Behavioral Neuroscience, 2023)
Aquatic species are capable of detecting infrasound (sub-20 Hz frequencies) which may be a source of urban pollution and have detrimental impacts on the environmental fitness of fish. Infrasound is generated by infrastructure, producing acoustic frequency peaks that are not discernable by humans. The presence of these frequencies may therefore impact the environmental wellbeing of aquatic laboratory animals, which are often housed in spaces adjacent to facilities producing infrasound. To investigate the potential impact of infrasound, we used wild-type zebrafish (Danio rerio) and exposed them to short periods of infrasound at either 5, 10, 15, or 20 Hz, or 0 Hz as a control group. A motion-tracking system was used to monitor fish movement in an open field test and arena location, distance moved, and immobility were quantified. There was a significant effect of 15 Hz which caused the fish to spend more time away from the infrasound source. The 20 Hz group also spent significantly less time in the zone closest to the speaker. There were no differences in distance moved or immobility between infrasound and control groups. These findings demonstrate that 15 Hz infrasound has aversive effects on zebrafish, causing them to move away from the sound source. To enhance environmental enrichment and wellbeing of aquatic laboratory animals, sources of infrasound pollution should be investigated and mitigated.